Separation of lawful operational-search measures from provocation of a crime։ standards established by the European Court of Human Rights - Barseghyan, Gevorg; Ghazinyan, Gagik (Bulletin of Yerevan University C: Jurisprudence, 2024)
The aim of this Article is to present a reasoned proposal for the criminalization of provocation of a crime as a result of a detailed study and systematic presentation of the criteria set by the European Court of Human Rights, taking into account the idea of lawful provocation of a crime and its features.To achieve this objective, the Article analyzes the criteria established by the European Court of Human Rights based on the examination of applications submitted to the Court concerning the legality and lawfulness of data obtained through operational-search activities. These criteria allow for the differentiation of lawful operational-search measures from provocation of a crime. Based on the content of these criteria, they have been conditionally classified into specific groups.As a result of the research conducted in the Article, it is proposed to comprehensively criminalize provocation of a crime, taking into account the successful practices of other countries and internationally recognized practices. At the same time, valuing lawful provocation, it is suggested to establish a criminal-legal norm that would consider it a circumstance excluding criminal liability.
Keywords: operational-search measure; legality of operational-search measure; provocation of crime; police trap; lawful provocation; European Court of Human Rights; European Convention on Human Rights; Criminal Code